KESALAHAN EJAAN HURUF DAN TANDA BACA PADA BAHAN AJAR MEMBACA MAHASISWA PBSI UNIVERSITAS WIRALODRA - Karomah, Siti; Triana Winata, Nana (Paramasastra : Jurnal Ilmiah Bahasa Sastra dan Pembelajarannya, 2022)
This study analysis spelling mistakes of letters and punctuation contained in "reading" teaching materials for PBSI students at Wiralodra University. The data taken in this study is the text of the book READING (Skilled in Language Through Reading) edition 2021. In this study, (1) knowing the wrong type of letters and punctuation in the book READING (Skilled in Language Through Reading); and (2) analyzing spelling errors in the use of letters and punctuation in the READING book (Skilled in Language Through Reading). This research is a qualitative research using descriptive method. The source of data in this study is the text in the READING book (Skilled in Language Through Reading). The method of data collection in this study is to use observation techniques and note-taking techniques. The results of this study indicate that there are 140 errors in the book entitled READING (Skilled Language Through Reading) which are divided into: 26 errors in punctuation (:), seven errors in punctuation (-), one error in sign (-), 20 errors in spelling italics, and 86 errors in spelling capital letters. Keywords: spelling mistakes, teaching materials, reading books